TV readings from the Spanish Transition. Informe Semanal and the first ephemeris of Change - Martín Jiménez, Virginia (Historia y Comunicación Social, 2014)
Informe Semanal, the Spanish Television news program that was born in 1973, consolidated during the transition to the democracy. Given the relevance of this program, this paper analyzes the readings that this informative television offered for the first ephemeris of the Transition. This study is based on the analysis of Informe Semanal, in-depth and face-to-face interviews with journalists who lived through the transition in Spain and an updated bibliography.